Propriedades vibracionais de nanotubos de carbono de parede tripla - Alencar, Rafael Silva (2012)
The study of the electronic, mechanical and vibrational properties of the carbon nanotubes with few layers is important for developing and improving models that could describe the behavior of multi-walled carbon nanotubes (MWNTs), which is the kind of nanotube most used in technological applications. Several theoretical and experimental studies have been conducted for understanding the behavior of single and double walled carbon nanotubes (SWNT and DWNT, respectively) under high hydrostatic pressures. However, the behavior of triple walled carbon nanotubes (TWNTs) under such conditions is still unknown. Here, we present a study of resonance Raman spectroscopy in TWNTs as function of hydrostatic pressure. We used paraffin oil and a mixture of methanol:ethanol in 4:1 ratio as pressure transmitting media (PTM) and a diamond anvil cell (DAC) for applying pressure. The evolution of the radial breathing modes (RBM) and the tangential modes (G band) as a function of pressure was analyzed in detail and compared with existing results for SWNTs and DWNTs. The Raman spectroscopy data show that the shielding effects of inner tubes in TWNTs are more pronounced than in DWNTs. The changes in the intensities of Raman modes were interpreted as being associated with pressure induced changes in the resonance conditions.